Boredom profiles, digital competence, and informal digital learning of Chinese among New Zealand adolescents: A person-centered approach - Zhao, Xian; Wang, Siyi; Zhang , Yi; Liu, Guangxiang Leon (Studies in Second Language Learning and Teaching, 2026)
Recognizing how the proliferation of digital technologies has expanded adolescents’ opportunities to engage with additional languages beyond formal classrooms, this study investigates informal digital learning of Chinese (IDLC) among New Zealand adolescents through a person-centered lens. It focuses on learners’ boredom and digital competence as key learner-internal factors closely associated with IDLC. Survey data were collected from 516 adolescent learners in six community schools and public high schools in Auckland. Using latent profile analysis, three boredom profiles were identified: low (31%), moderate (55%), and high (14%). Regression analyses showed that digital competence positively predicted IDLC overall, but the strength of this association differed across boredom profiles. Specifically, digital competence predicted IDLC only in the high-boredom profile, whereas the association was weak and nonsignificant in the low- and moderate-boredom profiles. Interestingly, heightened boredom proved to amplify the association between Chinese learners’ digital competence and IDLC. The findings demonstrate that boredom heterogeneity is central to understanding if and when digital competence translates into IDLC practice and indicate the value of person-centered approaches for advancing informal language learning research on Chinese in Anglophone contexts.